Behavior profiles and investments - Sanches, Daniela Rino (2019)
This dissertation studies the connection between behavior and investment decision. Investors are usually guided based only on risk-tolerance level and their behavioral bias is not considered for portfolio construction. We study ANBIMA’s (Associação Brasileira das Entidades dos Mercados Financeiro e de Capitais) investors profile and its relationship with financial decision-making and long-term portfolio allocation. Some authors suggest incorporating behavioral questions in the risk-profile questionnaire made by financial institutions. We find that demographic information does not explain behaviors in Brazilian individuals. Furthermore, investors profile is useful to understand some characteristics and behaviors that should be considered in long-term investments portfolio.